Tradisi Saparan sebagai Akulturasi Budaya dan Nilai Kearifan Lokal di Dusun Ploso, Kota Salatiga - Lin Lin Adhani; Siti Ekowati Rusdini (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the symbolic meanings and cultural acculturation embodied in the Saparan Tradition practiced in Ploso Hamlet, Salatiga City, through Clifford Geertz’s interpretive anthropological approach. The Saparan Tradition represents an important form of Javanese cultural heritage that integrates Islamic values with local wisdom and continues to be preserved across generations. Using a descriptive qualitative method, data were collected through participatory observation, in-depth interviews, and documentation involving traditional leaders, religious figures, and community members. The findings indicate that each stage of the Saparan ritual ranging from the determination of auspicious timing, preparation of offerings, village cleansing activities, to the communal feast contains symbolic meanings that reflect a harmonious relationship between humans, nature, and God. A central finding reveals a syncretic integration between Islamic values and local Javanese elements, where doa and tahlil led by religious leaders coexist with traditional offerings (sesaji) without negating their respective meanings. Islamic prayers function as expressions of gratitude and devotion to God, while offerings symbolize respect for nature, ancestors, and cosmic balance, forming a shared system of meaning within the community. Cultural symbols such as palawija, pala pendem, roasted chicken, and other ritual elements convey social, moral, and spiritual values, reinforcing gratitude, mutual cooperation, social solidarity, environmental awareness, and respect for ancestral heritage. Furthermore, the Saparan Tradition functions as a cultural mechanism that strengthens intergenerational bonds and preserves local identity amid globalization and modernization. These values also demonstrate relevance as contextual learning resources for Social Studies education based on local wisdom.